PEMBUATAN MEDIA PEMBELAJARAN INTERAKTIF DENGAN PERANGKAT LUNAK ISPRING PRESENTER DI SMAN 4 BANJARMASIN - Wagino Wagino; Nur Alamsyah; Zaenuddin Zaenuddin (JURNAL PENGABDIAN AL-IKHLAS UNIVERSITAS ISLAM KALIMANTAN MUHAMMAD ARSYAD AL BANJARY, 2015)
One media PowerPoint presentations are often used by teachers in presenting the teaching materials with the aim of male and female students can receive the material, but sometimes the making powerpoint mediocre can make them so bored, One good learning media and easy to use Tool iSpring software. iSpring Presenter is a presentation tool that converts files into flash form and shape SCORM / AICC,which is commonly used in the form of learning with e-learning LMS (Learning Management System).iSpring software is available in a free version (free) and paid.